(untitled) - Douglas Comer (New Jersey, 1989)
Introduction and overview; An overviwe of the machine and run-time environment; List and queue manipulation; Scheduling context switching; More process management; Process coordination; memory management; Interrupt processing; Real-time clock management; Message passing; Process - based hardware event handling...
Keywords: Macintosh (computer) - programming,operating systems ( computers ),system design